Infographic. Injury mechanisms and situational patterns of severe lower limb muscle injuries in male professional football (soccer) players: a systematic video analysis study on 103 cases - Della Villa, F.; Massa, B.; Bortolami, A.; Nanni, G.; Olmo, J.; Virgile, A.; Buckthorpe, M. (British Journal of Sports Medicine, 2024)
Muscle injuries are the most common type of injury in elite male football and constitute to about a third of total time loss.1 Hamstring injuries are on the rise and now account for nearly one in every four injuries.2 Most muscle injuries in football have short lay-off times (within 4 weeks), while 11% are severe (absence >28 days).1 These severe injuries are the most challenging ones to treat and are associated with a high risk of reinjury.